2003
DOI: 10.1046/j.1471-4159.2003.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated cocaine administration changes the function and subcellular distribution of adenosine A1 receptor in the rat nucleus accumbens

Abstract: Adenosine A 1 receptor (A 1 ) protein and mRNA is increased in the nucleus accumbens following repeated cocaine treatment. In spite of this protein up-regulation, A 1 agonist-stimulated [ 35 S]GTPcS binding was attenuated in accumbens homogenates of rats withdrawn for 3 weeks from 1 week of daily cocaine injections. Cellular subfractionation revealed that the discrepancy between total A 1 protein and G protein coupling resulted from a smaller proportion of receptors in the plasma membrane. The decrease in func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…A few in vivo studies demonstrated significant changes in the ultrastructural localization of GPCRs in response to modulation of extracellular activating neurotransmitter (Dumartin et al, 1998;Dumartin et al, 2000;Bernard et al, 2003;Toda et al, 2003;Stanwood and Levitt, 2007). However, in MPTP-treated mice, an experimental condition characterized by a significant increase in glutamatergic transmission in the subthalamic nucleus and globus pallidus (Mally et al, 1997;Fedele et al, 2001;Wichmann and DeLong, 2003), very little, if any, changes were induced in the subsynaptic and subcellular distribution of group I mGluRs in these nuclei (Kuwajima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A few in vivo studies demonstrated significant changes in the ultrastructural localization of GPCRs in response to modulation of extracellular activating neurotransmitter (Dumartin et al, 1998;Dumartin et al, 2000;Bernard et al, 2003;Toda et al, 2003;Stanwood and Levitt, 2007). However, in MPTP-treated mice, an experimental condition characterized by a significant increase in glutamatergic transmission in the subthalamic nucleus and globus pallidus (Mally et al, 1997;Fedele et al, 2001;Wichmann and DeLong, 2003), very little, if any, changes were induced in the subsynaptic and subcellular distribution of group I mGluRs in these nuclei (Kuwajima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting and subfraction of membrane bound receptor was conducted exactly as described previously (Toda et al, 2003). The antibody for receptors (Calbiochem, La Jolla, CA) was used at a 1:1000 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Separate animals were used for measuring total and membrane-bound protein, and, at 2-3 weeks after cocaine self-administration or yoked saline treatments (see above), animals were decapitated, the brain was rapidly removed, and the ventral pallidum was dissected on an ice-cooled glass plate. For total protein, the tissue was immediately frozen and stored at Ϫ80°C until analysis, and, for subfractionation, the tissue was immediately homogenized (Toda et al, 2003). After immunoblotting, band density was quantified using NIH Image 1.62.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of the A1-D1 receptor heteromer was reported over a decade ago following the demonstration of coimmunoprecipitation of adenosine A1 receptor (A1R) and D1R in fibroblast cells (Ginés et al, 2000), and shortly thereafter, its expression was shown by the same method in rat NAc (Toda et al, 2003). The A2-D2 heteromer, also identified by coimmunoprecipitation, was first shown in neuroblastoma cells (Hillion et al, 2002) and has since been shown to exist in living cells by FRET and BRET analysis (Canals et al, 2003;Kamiya et al, 2003).…”
Section: Adenosine-dopamine Receptor Heteromers: A1-d1 A2-d2mentioning
confidence: 97%
“…It has been suggested that the A1-D1 and A2-D2 heteromers have a discrete distribution in the basal ganglia, with selective expression along the striatonigral and stratopallidal pathways, respectively (Ferré et al, 2007;Franco et al, 2007;Fuxe et al, 2008), and functional studies indicate that these receptor complexes may be the molecular entities responsible, at least in part, for the antagonistic interactions between adenosine and dopamine receptors, functioning to uncouple the dopamine receptors from their respective G-proteins and dampen receptor signaling (Azdad et The ability of adenosine-dopamine receptor heteromerization to attenuate dopamine receptor function indicates that these receptor complexes are of relevance to dopamine transmission in the basal ganglia, and thus have a potential role in dopamine disorders. For example, following cocaine withdrawal the coimmunoprecipitation of A1R and D1R was reduced in rat NAc, indicating a reduction in heteromer formation (Toda et al, 2003). Similarly, using BRET methodology, cocaine was shown, through direct actions on D2R, to induce a conformational change in the A2-D2 complex, resulting in reduced BRETmax, potentially indicative of a reduction in heteromer expression .…”
Section: Adenosine-dopamine Receptor Heteromers: A1-d1 A2-d2mentioning
confidence: 97%